Nidificação do Urutau, Nyctibius griseus (Gmelin, 1789) (Aves: Nyctibiidae) em um ambiente urbano no Cerrado central (Lundiana: International Journal of Biodiversity, 2011)
This is a report on two nesting attempts by the Common Potoo (Nyctibius griseus) in an urban environment at Palmeiras de Goiás, Goias state, central Brazil. In December 12, 2006, a nest was found on a tree (Caesalpinia pothoroides), 2.8 m above the ground. This nest contained a white egg with dark red and brown patches. A few days later, no eggs were found in this nest. Other nesting attempt was recorded on October 9, 2007, when a chick was found in the same place used as nesting site in 2006. The young was not found in the next days. Our study is the first to document the nesting of N. griseus in the Cerrado core area.